2015
DOI: 10.1108/jcm-11-2014-1233
|View full text |Cite
|
Sign up to set email alerts
|

Perceived health and taste ambivalence in food consumption

Abstract: Purpose – This study aims to explore how certain consumer characteristics (dieting status, health motives and food values) together with products carrying ambivalent health and taste cues (light foods, convenience foods, “functional candies”) shape whether and why health and taste attributes are perceived as inclusive (“healthy is tasty” and “unhealthy is untasty”) or exclusive (“healthy is untasty” and “unhealthy is tasty”). Design/methodology/approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…Yielding to temptation and consuming fast food in an addictive manner can create internal conflict and cognitive dissonance, whereby the sense of pleasure derived by the consumption is quickly replaced by regret and remorse (Hofmann, Kotabe, & Luhmann, ). These negative feelings can also be attributed to increasing health consciousness among modern consumers, especially among the younger generation (Luomala et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Yielding to temptation and consuming fast food in an addictive manner can create internal conflict and cognitive dissonance, whereby the sense of pleasure derived by the consumption is quickly replaced by regret and remorse (Hofmann, Kotabe, & Luhmann, ). These negative feelings can also be attributed to increasing health consciousness among modern consumers, especially among the younger generation (Luomala et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, research findings indicated that consumers follow an unhealthy = tasty intuition, that is, they believe unhealthy food to taste better than healthy food (Liem, Toraman Aydin, & Zandstra, ; Raghunathan, Naylor, & Hoyer, ). In contrast, more recent findings indicated an opposing healthy = tasty view in consumers (Haasova & Florack, ; Landry et al, ; Luomala et al, ; Werle, Trendel, & Ardito, ). We believe that the healthy = tasty view is predominant in consumers because we think that the same cues on product packages can indicate health and taste to consumers.…”
Section: Introductionmentioning
confidence: 92%
“…The informants were asked whether they prefer taste or healthiness in their snacking to ensure as much variation in the data as possible. No definitions for these terms were provided as these preferences are seen to be formed through subjective experiential processes that, in turn, take inputs from numerous sources (Luomala et al, ). Further, as expected, the community interaction soon revealed that informants rarely engaged in snacking practices that were either just healthy or indulgent.…”
Section: Data Methods and Methodologymentioning
confidence: 99%